Severe Varicella Pneumonia. A Pediatric Case Presentation - Ariel Efrén Uriarte Méndez; Jesús Vila Díaz; Andrés Prieto Apesteguía (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
The case of a 12 years child old child, white skin, obese, from urban procedence and with a history of Crohn's disease who was admitted to the Intensive Care Unit at the "Paquito González Cueto" Pediatric University Hospital because of bloody diarrhea and severe dehydration is presented. After controlling the acute phase, the patient was taken to the gastroenterology room where he began presenting vesicular lesions on the trunk, diagnosed as varicella. A further complication appeared when the patient developed a severe pneumonia that quickly evolved into an acute respiratory distress syndrome which required transfer to intensive care unit with intensive therapeutic intervention, especially ventilatory management. Both radiologic and laboratory parameters were very characteristic, similar to those described in the literature. Despite intensive sustained treatment, the patient died a month after diagnosis was performed. Considering how infrequent this complication is in the case of children, it was decided to have the case published.